Independent Curriculum Implementation Training Ror the Learning Teacher Community in Setu District - Lilis Suryani; Rofiqotul Khusna; Novita Deviyanti; Nunuk Marlina; Munasri; Tine Mulyaningsih; Wiwin Zakiyah; Sri Yanti; Asri Binawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The independent curriculum is an entire unit and teachers are given the freedom to plan and carry out learning according to the characteristics and nature of the child, this is in line with the thoughts of Kihadjar Dewantara, as a national hero and the founder of national education, Ki Hadjar Dewantara's ideas about the education system through the among system have been widely studied and implemented in educational institutions throughout Indonesia. The development of the independent curriculum itself is optimized through the learning community in schools, between schools and the wider community. The participants can find out what an independent curriculum is, how to formulate learning objectives, determine dimensions in the five-dimensional student profile, and develop lesson plans using independent curriculum teaching modules. The existence of a pretest and post test shows that the knowledge and skills of the training participants show an increase as can be seen from the results of the post test where the average score increases to 78 from the average prestest score of 43, and the teaching modules produced by the participants show they understand and understand the curriculum independent.